Attitudes toward ICT and working with computers of the royal Malaysia police workforce / Ab. Latiff Ab. Rahman, Wan Narita Mustapha, Adnan Omar and Hajah Rugayah Hj. Hashim - Ab. Rahman, Ab. Latiff; Omar, Adnan; Hashim, Rugayah (Institute of Research, Development and Commercialization (IRDC), 2007)
One of the primary characteristics of policing of the next century will be the proliferation of technology as an important component of law enforcement. The successful law enforcer or policeman of the future will be marked by an ability to incorporate and directly apply a wide range of technology in their interactions with the public. More than simple data access, policing technology is increasingly being used as a means by which the police and the public interact. The overall objective of this study is to measure the attitudes of the Royal Malaysia Police workforce towards the use of information and communication technologies in policing and then ascertain the relationship between these attitudes and the policeman's job experience and productivity. With a response rate of 77.67% from the 600 questionnaires sent to 14 identified police headquarters throughout Malaysia, the results showed mediocre attitudes toward ICT and working with computers relative to usefulness, confidence, liking and anxiety. The findings of the study will outline important managerial implications related to introducing and implementing new technology uses svithin law enforcement personnel in Malaysia.